2019
DOI: 10.1088/2515-7655/ab4dc1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of surface inhomogeneity on the overcharge and lithium plating of graphite electrodes

Abstract: We seek to clarify phenomena involved in the overcharge of a graphite electrode in a lithium ion battery, including lithium (Li) plating. In Baker and Verbrugge (2019 J. Electrochem. Soc.), we developed a set of equations that can be used to treat Li plating and subsequent electro-dissolution, and we analyzed how the equation system behaved for a particle of graphite, a fundamental unit of the negative (porous) electrode in lithium ion cells. In this work, we employ the same governing equations, but we render … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Combining the macroscopic observations indicates that Li deposits form primarily in edge and fold locations of the cell where compression, electrolyte, and current distributions are expected to be most heterogeneous. This is in good agreement with the literature, where it was shown that Li deposits preferentially at electrode edges due to geometric effects 40 and electrode nonuniformities, 41 heterogeneous pressure 42 and compression, 43 and higher current densities. 44 Another observation confirming this is Figure 2c, showing the depositions on the anode of cell type C after the OEM cyc protocol; here all folds and edges are fully covered in Li depositions and decomposition products of the electrolyte, while the center parts of the electrodes are not fully covered by depositions.…”
Section: Resultssupporting
confidence: 93%
“…Combining the macroscopic observations indicates that Li deposits form primarily in edge and fold locations of the cell where compression, electrolyte, and current distributions are expected to be most heterogeneous. This is in good agreement with the literature, where it was shown that Li deposits preferentially at electrode edges due to geometric effects 40 and electrode nonuniformities, 41 heterogeneous pressure 42 and compression, 43 and higher current densities. 44 Another observation confirming this is Figure 2c, showing the depositions on the anode of cell type C after the OEM cyc protocol; here all folds and edges are fully covered in Li depositions and decomposition products of the electrolyte, while the center parts of the electrodes are not fully covered by depositions.…”
Section: Resultssupporting
confidence: 93%
“…This is likely to have important implications during fast charging, because Li plating is known to occur on particles or local regions of the graphite electrode that are fully lithiated. [60,61] The fact that the SEI resistance and composition (as measured by XPS, Figure 2) do not change measurably at various states of charge are indicative of the LBCO film remaining intact and functional, despite the volume changes expected in the graphite particles during cycling. This is also consistent with the continued suppression of Li plating over more than 500 cycles, which demonstrates that the ALD coatings provide a durable a-SEI under fast-charging conditions.…”
Section: Sei Impedance and The Role In Fast Chargingmentioning
confidence: 98%
“…This difference is probably related to the crystallite size of the graphite samples with the 50 nm and 23 μm particles having more exposed edges associated with their smaller graphite crystallites compared to the 790 nm and 20 μm samples. Lithium plating is known to occur on these reactive sites and edges . From this, it can be concluded that the impedance caused by the SEI formed at 0.1 C is a critical factor determining the cyclability of the electrodes at 12 C. The increased polarization due to the SEI layer formed at 0.1 C caused metal plating at 12 C.…”
Section: Results and Discussionmentioning
confidence: 99%